Experimental Study on the Discharge Coefficient of Bi-Swirl Coaxial Injectors - K. Ahn; B. J. Lee (Journal of Applied Fluid Mechanics, 2019)
An experimental study was carried out to investigate the effects of recess length and mixture ratio on the discharge coefficient of bi-swirl coaxial injectors with inner closed-type and outer open-type swirl injectors. Ten bi-swirl coaxial injectors were classified into two groups with different recess lengths. By independently varying the mass flow rates through the inner and outer injectors, the discharge coefficients of the injectors were obtained. Single-injection cold-flow tests indicated that the discharge coefficients of both the inner and outer swirl injectors were only marginally affected by the recess length and mass flow rate. Bi-injection cold-flow tests showed that the discharge coefficients of the inner swirl injectors were also almost constant, regardless of the recess length and mixture ratio. On the other hand, those of the outer swirl injectors in the tip-mixing and internal-mixing bi-swirl coaxial injectors with long recess lengths had significantly decreased with the increase in mixture ratio. A novel empirical equation for the discharge coefficient of the outer swirl injector in the internal-mixing bi-swirl coaxial injector is suggested through a linear regression analysis of the present test data. It was found that the present empirical equation could accurately predict the experimental data.